Development of Suspended Particulate Matter Empirical Equation for Tropics Estuary from Landsat ETM+ Data - Z Razak; A Zuhairi; S Shahbudin; Y Rosnan (Universitas Gadjah Mada, 2014)
Suspended Particulate Matter (SPM) essentially related to the total scattering of particles in the water column. It plays the role as a transport medium for pollutants, total load of organic and inorganic substance in the water phase. In this study, we have developed empirical relationship based on a strong relationship between Landsat near infrared (NIR) band and archived SPM data. The following were the power equations:SPM NE (mg/l) = 11.68x0.666SPM SW (mg/l) = 18.61x0.493where, x (TM4) is radiance of ETM+ NIR band 4 was developed under tropical atmospheric conditions. Using the above equation, the SPM concentration for Northeast and Southwest monsoon in the Pahang River estuary as a case study was determined. The mean SPM concentration and mean reflectance value during Northeast monsoon were 131.69 mg/l and 0.135 mg/l. The mean SPMconcentration value and reflectance were 95.94 mg/l and 0.078 mg/l during the Southwest monsoon. Generally, from remote sensing archive data and above equations, the SPM concentrations of Pahang River were successfully determined from 1999 to 2012.